2005
DOI: 10.1113/jphysiol.2005.094888
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide blunts myogenic autoregulation in rat renal but not skeletal muscle circulation via tubuloglomerular feedback

Abstract: This rat renal blood flow (RBF) study quantified the impact of nitric oxide synthase (NOS) inhibition on the myogenic response and the balance of autoregulatory mechanisms in the time domain following a 20 mmHg-step increase or decrease in renal arterial pressure (RAP). When RAP was increased, the myogenic component of renal vascular resistance (RVR) rapidly rose within the initial 7-10 s, exhibiting an ∼5 s time constant and providing ∼36% of perfect autoregulation. A secondary rise between 10 and 40 s brough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
125
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(147 citation statements)
references
References 73 publications
20
125
2
Order By: Relevance
“…The myogenic response is much faster, with a natural frequency of 0.1-0.2 Hz in the anaesthetized rats and 0.2-0.3 Hz in conscious animals (2,32,36,38,56,76,122,165,166). Essentially similar data regarding the kinetics of these mechanisms have been obtained through analyses of RBF responses to step changes in BP (84,85,102,175). These natural frequencies imply that the myogenic response can prevent changes in RBF in response to BP fluctuations that occur at intervals greater than 3-4 s, whereas TGF responds to slower BP fluctuations over intervals of 20 s or longer.…”
Section: Bp Variability and The Requirements For Protection Vs Regulsupporting
confidence: 60%
“…The myogenic response is much faster, with a natural frequency of 0.1-0.2 Hz in the anaesthetized rats and 0.2-0.3 Hz in conscious animals (2,32,36,38,56,76,122,165,166). Essentially similar data regarding the kinetics of these mechanisms have been obtained through analyses of RBF responses to step changes in BP (84,85,102,175). These natural frequencies imply that the myogenic response can prevent changes in RBF in response to BP fluctuations that occur at intervals greater than 3-4 s, whereas TGF responds to slower BP fluctuations over intervals of 20 s or longer.…”
Section: Bp Variability and The Requirements For Protection Vs Regulsupporting
confidence: 60%
“…15 Ang II levels also do not seem to modulate the relative contributions of MR and TGF. 27,38 We and others have shown that NO exerts a strong attenuating influence on the MR in the renal but not nonrenal circulations. 27,28 Importantly, this NO influence depends on functional TGF, 27,28 suggesting neuronal NOS in macula densa cells as the source.…”
Section: Discussionmentioning
confidence: 99%
“…27,38 We and others have shown that NO exerts a strong attenuating influence on the MR in the renal but not nonrenal circulations. 27,28 Importantly, this NO influence depends on functional TGF, 27,28 suggesting neuronal NOS in macula densa cells as the source. Given the probable role of Cx40 in TGF signal transduction and the possibility of NO modulation of connexin conductance, 25,39 we postulated that the absence of Cx40 impacts on NO effects on the renal MR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations